Deep natural language processing and AI applications for industry 5.0 - Tanwar, Poonam, 1979-; Saxena, Arti, 1984-; Priya, C., 1979- (Advances in computational intelligence and robotics (ACIR) book series., 2021)
"This book is a collection of contributed chapters of latest research findings, ideas, and applications in the fields of Natural Language Processing and their applications, Computational Linguistics, Deep NLP, Web Analysis, Sentiments analysis for business and industry"--